City elements propelling city brand meaning-making processes: Urban reminders, the arts, and residential behavior. (September 2018) - Green, Amelia; Grace, Debra; Perkins, Helen
City branding literature discounts the nonmarketer-controlled aspects of city brand meaning co-creation as part of everyday, sociocultural meaning-making. Engaging a fundamental gap within this theoretical oversight, the present article explores how socially constructed and, thus, inherently uncontrollable elements of the city communicate symbolic messages about the city during the course of daily urban life. Specifically, the article contributes to marketing theory by conceptualizing how (1) urban reminders, (2) the arts, and (3) residential behavior emit symbolic messages in highly interrelated ways that see these elements propel the interconnected meaning-making processes enveloping city brands. Subsequent critical discussion further demonstrates how the more holistic view of city brand meaning-making processes that we develop opens up a fresh lens to grasp more of city brand meaning co-creation, advance intellectual debates around city branding, and, ultimately, expand the frontiers of marketing theory.